Analisis Yuridis Tindakan Kriminal Doxing Ditinjau Berdasarkan Undang Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi - Muhammad Kamarulzaman Satria; Hudi Yusuf (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The digitalization era and the development of information technology have heightened the importance of personal data protection as a part of human rights. This study aims to analyze the implementation of Law Number 27 of 2022 on Personal Data Protection (PDP Law) in Indonesia, compare it with international regulations, and evaluate its effectiveness in safeguarding citizens' personal data. The methodology employed is normative juridical analysis, examining relevant legal documents and related literature to identify and understand the framework for personal data protection. The findings indicate that although the PDP Law provides a strong legal basis for personal data protection, challenges remain in terms of law enforcement, public awareness, and private sector compliance. This research proposes enhanced inter-agency cooperation and regulatory strengthening as subsequent steps to optimize personal data protection in Indonesia.